1, 3-Carboboration of iodonium ylides. Issue 22 (24th February 2020) - Gazis, Theodore A.; Mohajeri Thaker, Bayan A. J.; Willcox, Darren; Ould, Darren M. C.; Wenz, Jan; Rawson, Jeremy M.; Hill, Michael S.; Wirth, Thomas; Melen, Rebecca L.
Abstract : Herein, we disclose the utilisation of iodonium ylides to access a range of boron dienolates. Abstract : Herein, we disclose the utilisation of iodonium ylides to access a range of boron dienolates. Heating of acyclic iodonium ylides in the presence of different aryl boranes leads to the formation of rare 1, 3-carboboration products. This methodology could not be expanded to cyclic iodonium ylides which instead formed a Lewis acid–base adduct. Products proved to be remarkably stable under a wide range of conditions allowing for their long term storage.